Total ionizing dose analysis of SAR ADC for space applications - Lim, Nadia (2024)
This study investigates the performance of a Successive Approximation Register (SAR) Analog-to-Digital Converter (ADC) under Total Ionizing Dose (TID) conditions, identifying the TID-sensitive blocks and their impact on overall performance. TID models were developed to simulate two primary effects: threshold voltage shifts in the comparator and leakage current increase in the sampling and capacitor digital-to-analog converter (CDAC) switches. Models were developed based on experimental data from literature, and using a combination of Berkeley Short-Channel IGFET Model (BSIM) device modeling and circuit-level modeling. SPICE simulations, employing transient and spectral analyses, revealed that threshold voltage shifts in the comparator have minimal impact on noise characteristics and overall performance due to the comparator's robust design features. Conversely, leakage effects in the sampling and CDAC switches caused slight deviations in the output signal due to erroneous voltages generated through the switches, resulting in significant degradation in the ADC performance parameters. Combined TID effects revealed further performance degradation due to compounded errors resulting from erroneous voltages fed to the comparator and the TID-induced on-resistance variability of the sampling switches. Results from this analysis provide valuable insights into the SAR ADC's suitability for space applications and highlights the critical effects in the design blocks that significantly impact overall ADC performance under radiation.